Anthropogenic versus natural control on lacustrine sediment yield records from the French Massif Central. (30th October 2022) - Chassiot, Léo; Simonneau, Anaëlle; Chapron, Emmanuel; Di Giovanni, Christian
Abstract: A quantitative assessment of historical sediment yields (SY) was performed using sediment budgets from lacustrine records located in the Mont Dore and Cezallier volcanic provinces (French Massif Central). A source-to-sink approach combining hydro-acoustic images, organic geochemistry (Rock-Eval and quantitative organic petrography) and radiocarbon dating of sediment cores has been adopted on three lake-catchment systems, namely Pavin, Chauvet and Montcineyre. SY was estimated from the quantification of red Amorphous Particles (rAP), a terrigenous organic tracer identified in both soils and sediments. Historical SY range between 3 and 320 t km −2 .yr −1, which is comparable to the magnitude reached in other European lake-based SY records in similar geographical and climatic settings. Comparison of recent SY with predicted values of soil erosion rates from the RUSLE2015 model highlights large differences linked to scale differences between the model at plot scale and lake-based SY reflecting erosion export from the catchment to the lake. In this sense, the role of peatlands as sediment traps within two studied catchments must be considered to explain the large differences between modelled soil erosion rates and reconstructed SY data. SY differences between sites can be firstly attributed to morphology, size and lithology of the catchments as well as to vegetation cover whereas fluctuations reconstructed for each record seem to be mainly related to human-induced land use management. Historical SY from Chauvet and Montcineyre synchronously recorded two events in 850 CE and 1450 CE, respectively. The first marked the rise of SY to their maxima following land-use changes in the catchments. Nearby palaeoenvironmental records from Lake Aydat, Chambedaze peatland, and Espinasse marsh suggest this rise was consecutive to intensification of agro-pastoral activities recorded at regional scale. The second event followed a land-use shift characterized by a ten to fifteen-fold decrease in SY values. The driver remains unclear but could be possibly related to historical events causing a demographic decline (i.e., the Black Plague and/or the Hundred Years War) and/or cultural adaption in response to the onset of the Little Ice Age. Overall, both records suggest erosion in the area has been historically more susceptible to human-induced land use change rather than to precipitation and temperature changes induced by climate variability of the past millennium.